Proof of Concept Trial of Dronabinol in Obstructive Sleep Apnea - Prasad, Bharati; Radulovacki, Miodrag G.; Carley, David W. (Frontiers in Psychiatry, 2013)
Study Objective: Animal data suggest that Δ9-TetraHydroCannabinol (Δ9THC) stabilizes autonomic output during sleep, reduces spontaneous sleep-disordered breathing, and blocks serotonin-induced exacerbation of sleep apnea. On this basis, we examined the safety, tolerability, and efficacy of dronabinol (Δ9THC), an exogenous Cannabinoid type 1 and type 2 (CB1 and CB2) receptor agonist in patients with Obstructive Sleep Apnea (OSA). Design and Setting: Proof of concept; single-center dose-escalation study of dronabinol. Participants: Seventeen adults with a baseline Apnea Hypopnea Index (AHI) ≥15/h. Baseline polysomnography (PSG) was performed after a 7-day washout of Continuous Positive Airway Pressure treatment. Intervention: Dronabinol was administered after baseline PSG, starting at 2.5 mg once daily. The dose was increased weekly, as tolerated, to 5 mg and finally to 10 mg once daily. Measurements and Results: Repeat PSG assessments were performed on nights 7, 14, and 21 of dronabinol treatment. Change in AHI (ΔAHI, mean ± SD) was significant from baseline to night 21 (−14.1 ± 17.5; p = 0.007). No degradation of sleep architecture or serious adverse events was noted. Conclusion: Dronabinol treatment is safe and well-tolerated in OSA patients at doses of 2.5–10 mg daily and significantly reduces AHI in the short-term. These findings should be confirmed in a larger study in order to identify sub-populations with OSA that may benefit from cannabimimetic pharmacologic therapy.